2015
DOI: 10.4103/2156-7514.154351
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fibroid Embolization for Symptomatic Fibroids: Study at a Teaching Hospital in Kenya

Abstract: Objective:Characterization of magnetic (MRI) features in women undergoing uterine fibroid embolization (UFE) and identification of clinical correlates in an African population.Materials and Methods:Patients with symptomatic fibroids who are selected to undergo UFE at the hospital formed the study population. The baseline MRI features, baseline symptom score, short-term imaging outcome, and mid-term symptom scores were analyzed for interval changes. Assessment of potential associations between short-term imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…We did not observe any association between change in symptom severity score and uterine volume, consistent with an earlier report from our group [ 12 ]. However, an interesting observation is that those with a higher number of fibroids prior to UFE have reported a greater improvement in symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We did not observe any association between change in symptom severity score and uterine volume, consistent with an earlier report from our group [ 12 ]. However, an interesting observation is that those with a higher number of fibroids prior to UFE have reported a greater improvement in symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…The uterine volume, volume of the dominant fibroid and number of fibroids prior to UFE were ascertained independently by two radiologists using the pre-UFE pelvic MRI examination. Volumes were determined by measuring the maximum extent of the uterus and dominant leiomyoma in three planes and multiplying the product by 0.5233 (ellipsoid volume formula) [ 12 ]. An experienced interventional radiologist (NH) carried out embolisation under conscious sedation using spongostan gelfoam (ETHICON) in the hospital’s cardiac catheterization suite via a transfemoral approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uterine fibroid embolization is a relatively new technology in Africa with few studies documenting its use. The studies identified on UFE have studied other UFE aspects such as radiological features and response of fibroids after UFE and short-term quality of life changes for up to a year [18,29]. Our study has sought to document the long-term quality of life following UFE in a predominantly black population in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol and procedures for UAE at the Aga Khan University Hospital are reported elsewhere. [7] Blood was collected in plain vacutainers, and delivered to the biochemistry laboratory within 60 minutes. This was centrifuged, and sera frozen at -20°C until analysis using the Beckman Coulter Gen. II assay (Beckman Coulter Inc., USA).…”
Section: Study Protocolmentioning
confidence: 99%